Pengalaman Musikal dalam Teori Kecerdasan Majemuk Howard Gardner - Untsa Akramal Atqa; G.R. Lono Lastoro Simatupang; Royke B. Koapaha (Universitas Gadjah Mada, 2019)
The interest in music studies from various disciplines has increased in recent years. This is because the results of studies that show musical abilities are related to non-musical abilities. One example is research on music and intelligence. Music with intellectual intelligence and emotional intelligence has been proven to have strong relationships. Therefore, this paper was made as one of the studies on the relationship of music with intelligence, especially multiple intelligences that have not been widely studied before. The research method used is the study of literature. This literature study aims to build and construct conceptions more strongly based on empirical studies that have been done before.